PUBLIC-PRIVATE PARTNERSHIPS AND LEVERAGED PRIVATE EQUITY FINANCING - Callender, Guy (The journal of contemporary issues in business and government, 2008)
The popularity of outsourcing has remained undiminished in Australia as governments seek to achieve the goals of economic efficiency, debt minimisation and service delivery. The emergence of Public-Private Partnerships (PPPs) or Private Finance Initiatives (PFIs) has resulted in a more complex phase of the outsourcing process and has coincided with the increased opportunities for private equity funds to successfully bid for PPP/PFI contracts. Private equity capital is a fundamental feature of a capitalist economy; however, the aggregation of large amounts of private funds to participate in PPPs/PFIs represents a new trend that should be evaluated by public managers when negotiating PPPs at the contract formation and contract management stages of such arrangements. While the process of creating a PPP or PFI may be transparent, the financial progress of the project over a 20-30 year period may not be adequately disclosed, so that the expectations of both government and civil society cannot be fully assessed. This paper will draw on certain recent PPP experiences, focusing on some features of private equity that have created unexpected risk to the state and to taxpayers. The research suggests that the financial and operating structures of PPPs must meet the needs of the state to solve its financial and service delivery dilemmas without creating additional risk by uncritical acceptance of complex, highly leveraged contracting arrangements with private equity groups.